Design of a tropical rain - Disaster alarm system: A new approach based on wireless sensor networks and acoustic rain rate measurements - Libatique, Nathaniel Joseph C (Archīum Ateneo, 2009)
This paper discusses the design of a broadband wireless network infrastructure which itself is a rain measurement platform for applications such as disaster alarm and sudden hazard decision management systems. A sensor testbed is setup which consists of a hybrid broadband wireless network in conjunction with real-time acoustic rain rate point sensors and complementary rain gauges. The testbed simulates the commercial deployment of a line-of-sight wireless backbone (implemented via a 26 GHz line of sight link) and broadband wireless access network at 5 GHz and 2.4 GHz. Combined wireless signal fade, acoustic power and tipping bucket rain rate measurements over a several month span indicate the feasibility of using rain-induced attenuation and fade durations to trigger imminent-hazard alerts.